2018
DOI: 10.1177/1833358318781099
|View full text |Cite
|
Sign up to set email alerts
|

Systemic analysis of medication administration omission errors in a tertiary-care hospital in Quebec

Abstract: The interdisciplinary committee formulated 10 main recommendations related to these 7 categories, including 3 for IV therapy and 4 for failure in using or creating/updating the MAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
(25 reference statements)
0
8
0
1
Order By: Relevance
“…Consistently amongst the commonest three subtypes of medication administration error [41] Harm difficult to quantify, but an important, potentially remediable problem [42] P = within prescribing; A = within administration Box 2. Case study: using incident data to further investigate identified areas of risk…”
Section: Dosing Errors (Pa)mentioning
confidence: 99%
“…Consistently amongst the commonest three subtypes of medication administration error [41] Harm difficult to quantify, but an important, potentially remediable problem [42] P = within prescribing; A = within administration Box 2. Case study: using incident data to further investigate identified areas of risk…”
Section: Dosing Errors (Pa)mentioning
confidence: 99%
“…Individuals confronted by stress and intimidating behaviour can also affect medication errors [ 8 ]. While past studies have considered who was responsible for, or contributed to, the occurrence of the medication error, there has been little emphasis on patient and family involvement [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Such errors cause patients to suffer increased financial burden, unnecessary discomfort and prolonged hospitalization, morbidity and mortality, rendering these errors clinically significant. 6,7 Omission of drugs such as antimicrobial agents has the potential to cause patient harm through increased risk of treatment failure and development of more resistant strains of pathogenic microorganisms. 8,9 The earliest days of inpatient care are perhaps of the utmost significance in a patient's recovery; therefore, any omission of medications during this period has the possibility of increasing morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…When the frequency of medication omission errors was compared, parenteral drugs (70.8% vs. 25.3%, [p=0.0001]), afternoon shift (48.5% vs. 15.8%, [p=0.0001]), and anti-infective medications (69.1% vs. 39.4%, [p=0.0001]) were found to be the most frequently omitted medications. There were also considerably more medication omissions in patients prescribed with more medications (median number: 4, I QR [2,6] vs. median number: 2, IQR [2, 4], [p=0. 0.001]).…”
mentioning
confidence: 99%